Non random distribution patterns of supernumerary segments and B chromosomes in Dichroplus elongatus (Orthoptera) - Remis, M.I. (1998)
Dichroplus elongatus is a grasshopper, which exhibits parallel polymorphisms for B chromosomes and supernumerary segments in chromosomes S10 (SS10), S9 (SS9) and M6 (SS6) in natural populations of Argentina. The patterns of simultaneous variation of different forms of supernumerary heterochromatin from 7 populations of two biogeographic provinces located at Northwest and East regions of this country were analysed. Spatial chromosome differentiation for all heterochromatic variants was observed. Different degree of differentiation among populations for supernumerary segments, evaluated through F(ST), was observed. This suggests that genetic drift and migration may not be the only factors involved in the maintenance of the detected chromosome patterns. The differentiation for SS9 and SS10 may be explained mainly by heterogeneity within the Northwest Region. On the contrary, the differences for SS6 and B chromosomes explained through isolation by distance. However, the absence or the low frequency of both chromosome mutations in some populations may not be explained by historical factors. A principal component analysis showed that the patterns of chromosome variation do not agree with the geographical distribution of the populations. The relationship between frequencies of each supernumerary segment and B chromosome depends on the segment. An analysis of partial correlation showed that the frequencies of B chromosomes were positively correlated with the frequency of SS6 and negatively with the frequency of the SS10. In agreement with this, a multiple regression analysis of B chromosome frequency on supernumerary segment frequencies depends on the incidence of SS6 and SS10. The covariation of the heterochromatic forms may act as another factor that establish limits to stochastic factors, may also affect the probable negative selection on B, and could be involved in the non random pattern detected in D. elongatus.